A simple and sensitive silver-staining method for detecting AFLP markers in fungi - S Zhong; B J Steffenson (Fungal Genetics Reports, 2000)
A simple and fast silver-staining method is described for detecting amplified fragment length polymorphism (AFLP) markers separated in denaturing polyacrylamide gels. The silver-staining method produced a good degree of resolution and sensitivity and could be widely applicable in AFLP analyses of fungi.